PENGUATAN SEKTOR-SUBSEKTOR EKONOMI DALAM UPAYA PENINGKATAN PEMBANGUNAN EKONOMI DAERAH - Wahyudi, Setyo Tri (Journal of Indonesian Applied Economics, 2008)
This research  aims at identifying the potentials of economic sectors andproblems  related  in    district  Jember  in  East  Java,  for  designing  thedevelopment  strategy.  Based  on  purposive  sampling  and  qualitativeapproach, this research found that the agriculture and marine sectors areof the potentials which need to develop much.Keywords: economic potentials sectors, qualitative approach